Kreativitas Guru Bahasa Inggris dalam Mengajar Daring - Tobroni, Imam (Educreative : Jurnal Pendidikan Kreativitas Anak, 2021)
This study aims to determine the description of the creativity of teaching some English teachers in Yunior High School in Banyumas regency during pandemic covid-19, particularly in using online learning media. The method used in the research is descriptive qualitative. One of online learning challenge is boredom, less motivation, uninteresting learning, many homeworks, and also the students don’t go to school for a long time and they will disturb the learning effectivity. In this case, teachers creativity is primarly needed so teachers can manage online learning to be an interesting class and it will motivate students to study and in turn it will also improve students ’achievement. The results show that from 8 English Yunior High School teachers in Banyumas regency researched, found many various way of teaching online using online media. The creativity that has done is the planning, implementing, dan evaluation in teaching online. There are 3 online media used in planning & implementing, they are Whatsapp group, Google Classroom, and Video Converence (Zoom/Google meet). In addition there are 5 online media used in evaluation, they are Ms. Word, Google Forms, Quizizz, Ms. Forms. And Online Crossword. From this study concluded that English teachers creativity is very good in which each teacher has his/her own creativity adapted with the students’ situation & condition and it becomes the other choice of teaching online model for readers.